If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 = 15 + -12x Reorder the terms: 7 + 3x = 15 + -12x Solving 7 + 3x = 15 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 7 + 3x + 12x = 15 + -12x + 12x Combine like terms: 3x + 12x = 15x 7 + 15x = 15 + -12x + 12x Combine like terms: -12x + 12x = 0 7 + 15x = 15 + 0 7 + 15x = 15 Add '-7' to each side of the equation. 7 + -7 + 15x = 15 + -7 Combine like terms: 7 + -7 = 0 0 + 15x = 15 + -7 15x = 15 + -7 Combine like terms: 15 + -7 = 8 15x = 8 Divide each side by '15'. x = 0.5333333333 Simplifying x = 0.5333333333
| -3w-(-9)=12 | | P(t)=5t^2+12t+2 | | z/3.5=4 | | 47-11=36 | | 2(12.5-4x)+2x=11.5 | | 9-16y^2=0 | | 42/0.2 | | 5(7a-8)=-320 | | 12z=168 | | 2(12.5-4x)+2y=11.5 | | 4y+2.6y=36 | | 2x+7=x+7+x | | 3x-2sin(x)+7=0 | | (a-bi)(3+5i)=0 | | 9x^3-6x^2-6x+4=0 | | 2(w+3)-8w-1= | | 5x+14=4+3x | | 7(b-4)=-84 | | 3z+20=(-55) | | x-x*.17=24070 | | 7x-4+2x=5 | | n-16=21 | | 8(2n+6)=112 | | 8.304/16 | | 4x+10-6+4=20 | | 2/5x=6/35 | | 2xsquare=8x | | 4(6-5x)=164 | | -8w+10=5 | | 2(3x-18)=0 | | P(X)=x^3-4x^2+8 | | -2xa+4a=0 |